A biomechanical study of grip and pinch strength among Malaysian elderly population - Taha, Zahari; Sulaiman, Ruhaizin (Universiti Putra Malaysia Press, 2011)
The physical strength of the elderly aged above 60 years is typically 10 to 30% less than the young adult population of ages between 25 to 35 years. This reduction of strength has a strong impact on the activity of the daily living (ADL) of the elderly population. There has been little research done studying on the physical strength of the elderly population in Malaysia. The objective of this study was to determine the static strength of the elderly population in Malaysia. In particular, the grip and pinch strength were investigated as these two static strengths are extensively used in their instrumental activity of daily living (IADL). The results were then compared to the strength of the university students. A total of 30 subjects (15 males and 15 females) participated in the study. Their age ranged between 60 to 83 years, with the mean of age of 67.1 years. The comparison group comprised a total of 30 university students (20 male, 10 female) aged between 23 to 24 years, with the mean of age of 23.2 years. Grip and pinch strengths of both groups were measured and analysed using a descriptive statistics. It was found that the elderly male subjects are stronger in both strength measurements than their female counterpart. The 95th percentile of the female grip strength was slightly lower than that of the male while the male pinch strength was 31.07% higher. It was also found that the male students had higher strengths compared to the females. The grip strength of the elderly was 30.66% lower than the university student, while their pinch strength was 13.42% lower. Both static strengths of the elderly were found to be lower than those of the university students. This supported the research hypotheses postulating that the static strength had a negative correlation with age. In terms of gender differences, the male subjects were found to be stronger than the females.